THE RELATION AGE WITH OCCURENCE OF STRESS SANTRI IN PONPES NURUL FALAH COUNTRYSIDE BANJAR AGUNG DISTRICT OF PURI SUB-PROVINCE OF MOJOKERTO - Basuki, Duwi; Dui Miswanto, Dadang (JURNAL KEPERAWATAN BINA SEHAT, 2011)
Many event, condition or occurence able to as pencetus of stres. Start from small occurence or event come up with bigly [of] its influence. Big the so small influence of the event also will base on each one. Phenomenon which happened many many santri residing in maisonette environment of pesantren natural stres. The research is to know the relation age with occurence of stress santri in Ponpes Nurul Falah Countryside Banjar Agung District Of Puri Sub-Province of Mojokerto. The Desain Research is Cross sectional. The population is all santri in Ponpes Nurul Falah Countryside Banjar Agung District Of Puri Sub-Province of Mojokerto counted 125 people. The election of sampel with purposive sampling counted 56 responder. The independent variable is age. The dependent variabel is occurence of stress santri. Data obtained with Instrument sheet of Depression Anxiety Stress Scale ( DASS 42). The result of research show most responder age of[is including adolescent early counted 31 people ( 55,4%), most natural responder light stres counted counted 30 people ( 53,6%) and there is relation age with occurence of stress santri by using statistical test Spearmen Rho by result of p = 0,05 that is 0,000 < 0,05. So that the importance of effort able to lessen stres santri in maisonette of pesantren for example athletics regularly, providing nursemaid which can give konseling to its natural him problem of either in maisonette environment of pesantren or in schoolKeyword : age, stres, santri